The Relationship Between Body Mass Index with Uric Acid Levels at Puskesmas Kubutambahan II in 2025 - Widana, I Nengah Krisna Murthi Ary; Rahmayani, Irma; Budiawan, Made; Arsani, Ni Luh Kadek Alit (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Population growth has contributed to gout becoming a global health issue with a significant prevalence rate. According to WHO data in 2017, the global prevalence of gout reached 34.2%. In Indonesia, the prevalence of doctor-diagnosed gout among the population aged ≥ 15 years reached 7.30%, with Bali recording 10.46% and Buleleng Regency reaching 12.93% (Riskesdas, 2018). WHO has recognized Body Mass Index (BMI) as the best epidemiological measure to evaluate overweight or underweight and is a potential risk factor for various metabolic problems, including increased uric acid levels. This study aimed to determine the relationship between BMI and uric acid levels at Kubutambahan II Public Health Center in 2025. This study used an observational analytic design with a cross-sectional approach, aiming to analyze the relationship between variables at a single point in time. Secondary data were used, consisting of medical records with a sample size of 45 patients. Data analysis included univariate analysis to determine the frequency distribution of the independent variable (BMI) and dependent variable (uric acid levels), as well as bivariate analysis using the Spearman correlation test to examine the relationship between the two variables. The results showed a weak positive correlation between BMI and uric acid levels, with a correlation coefficient (r) of 0.344 (0.20-0.399) which Indicated an increase in BMI tends to be followed by an increase in uric acid levels. The results also showed a p- value of 0.021 (< 0.05), indicating a significant relationship between BMI and uric acid levels.